Heterogeneity measurement of the impact of the rural land three rights separation policy on farmers’ income based on DID model - Hu, Shanshan; Fu, Zhaogang; Chen, Zhen; Xue, Qingyi (Frontiers in Sustainable Food Systems, 2024)
Introduction As is well known, the policy of separating three rights is another important milestone in China’s land system reform. This policy has been in effect for 10 years and is of great significance to the livelihoods of rural families. In the implementation of policies, some farmers have obtained more land management rights, but some farmers have temporarily lost their land management rights. Existing research has shown that there is no consensus on the effect rural land three rights separation on increasing farmers’ income, especially in terms of heterogeneity research, which is more scattered. Methods We will use the latest national fixed observation point data from the Ministry of Agriculture and Rural Affairs from 2011 to 2020, as well as data from Peking University Treasure Database, West Lake Law Library Database, China Statistical Yearbook, and China Rural Statistical Yearbook. This paper matched the unbalanced panel data of 9,846 rural household samples from 30 provinces except Hong Kong, Macao, Taiwan and Xizang, and conducted an empirical study using the multi time point DID method. Result The overall result shows that the policy of three rights separation of rural land can improve the income of farmers, and the impact is more obvious after the promulgation of relevant laws. From the perspective of farmers’ heterogeneity, farmers with more training, food crop planting farmers, and farmers with relatively large land scales are more significantly affected by the policy’s income increase effect. Discussion Scholars have yet to find a good explanation for how the rural land three rights separation affects farmers’ income. In this article, it appears that the three rights separation policy has promoted the increase of farmers’ income through intermediary mechanisms such as investment level, credit level, and non-agricultural employment level.